RELASIONAL DESAIN ACTIVY DIAGRAM SISTEM INFORMASI AGEN TRAVEL - Handie Pramana Putra; Sugiarto; Hendra Maulana; Evi Triandini; Praja Firdaus Nuryananda (Prosiding Seminar Nasional Teknologi dan Sistem Informasi, 2022)
Utilization of technology properly is one form of solution that can be utilized by travel agents. Travel agents are intermediary, travelers will be greatly helped by the use of technology because it can save in all respects, both time, cost and energy because it can be reached anywhere and anytime and can easily view information on time and ticket availability. In designing an information system, it is necessary to have activity diagrams and flowcharts to describe the flow of a program from each process, another function is to place or simplify an explanation of the existing process, that way, a flowchart or flowchart will be more easily understood by everyone.